BABASAN JEUNG PARIBASA DALAM TAFSIR “SESEMPERAN TINA IBER” KARYA SAYUB SAYIDIN - Roni Nugraha (Institut Agama Islam Persis Bandung, 2021)
Abstract Persis as an organization centered at the Pasundan level, Persis uses Sundanese as a medium of da'wah, this is evidenced by the publication of the Sundanese language magazine At-Taqwa (1937). This magazine was discontinued during the revolution and was republished in 1949-1954. In 1967 the Bandung Branch together with E. Abdullah published Iber magazine which lasted until 2014. This Sundanese language magazine which lasted for approximately 47 years presented various Islamic studies, ranging from the rubric of interpretation to istifta. This research method uses qualitative methods. According to Bodgan and Taylor, qualitative methodology is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. This study will try to examine the Sundanese interpretation of Sayub Sayidin. The primary data source of this research is Sayub Sayidin's interpretation in Semperan Mutiara Iber. Judging from the source of his interpretation, Sayub Sayidin's commentary published in Iber magazine can be categorized as a biriwayat/bilmatsur interpretation. There are 17 chapters used by Sayub Sayidin to interpret the verses of the Koran. Babasan is deliberately presented as Sayub's criticism of the reality of people's lives, with the hope that through babasan in interpreting the Qur'an there will be a change in people's mindset. Keywords: Sundanese, Tafsir, Persis. Abstrak Persis sebagai organisasi yang berpusat di tatar Pasundan, Persis menjadikan bahasa Sunda sebagai media dakwah, hal ini terbukti dengan diterbitkannya majalah berbahasa Sunda At-Taqwa (1937). Majalah ini sempat berhenti pada masa revolusi dan kembali terbit pada tahun 1949-1954. Pada tahun 1967, persis cabang Bandung bersama E. Abdullah mengeluarkan majalah Iber yang bertahan hingga tahun 2014. Majalah bahasa sunda yang bertahan kurang lebih selama 47 tahun ini menyajikan berbagai kajian keislaman, dari rubrik tafsir hingga Istifta. Metode penelitian ini menggunakan metode kualitatif. Menurut Bodgan dan Taylor, metodologi kualitatif sebagai prosedur penelitian yang menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang dan perilaku yang dapat diamati. Penelitian ini akan mencoba mengkaji tafsir Sunda dari Sayub Sayidin. Sumber data primer dari penelitian ini adalah tafsir Sayub Sayidin dalam Sesemperan Mutiara Iber. Ditinjau dari perspektif sumber tafsir, tafsir Sayub Sayidin yang dipublikasikan pada majalah Iber bisa dikategorikan sebagai tafsir biriwayat/bilmatsur. Terdapat 17 babasan yang digunakan Sayub Sayidin untuk menafsirkan ayat-ayat al-Quran. Babasan tersebut sengaja didatangkan sebagai kritik Sayub terhadap realitas kehidupan masyarakat yang dengannya ia berharap melalui babasan dalam menafsirkan al-Quran terjadi perubahan pola pikir di kalangan masyarakat. Kata kunci: bahasa sunda, Tafsir, Persis.